PERBEDAAN PENURUNAN TEKANAN DARAH PADA IBU HAMIL TRIMESTER 1-3 DENGAN HIPERTENSI GESTASIONAL YANG DIBERIKAN REBUSAN LABU SIAM DAN OBAT ANTI HIPERTENSI DI PUSKESMAS RAWAT INAP CIDAUN TAHUN 2025 - Barbara, Maria Awaldina Dua; Susanti, Futri (SINERGI : Jurnal Riset Ilmiah, 2025)
Background: Based on data from the Cianjur Health Service, hypertension in pregnancy is the most common cause of death, namely 15-20 people per year. Gestational hypertension is included in pregnancy complications that can increase the risk of harm to the mother and fetus, treatment can be done pharmacologically and non-pharmacologically, one of which is using Chayote Decoction. Objective: To determine the difference in blood pressure reduction in pregnant women in the 1st-3rd trimester with gestational hypertension who are given antihypertensive drugs and chayote decoction at the Cidaun Inpatient Health Center in 2025. Research Method: Using a Quasi-Experiment design with a nonequivalent control group design, a sample of 80 people, divided into two groups, experimental and control, the sampling technique is total sampling. The instruments used are sphygmanometers and observation sheets. With numerical comparative data analysis of 2 unpaired groups. Results: Based on the results of the T test, the systolic blood pressure in the experimental group and the control group differed by 0.07 with a p-value = 0.970. Meanwhile, there was a difference in diastolic blood pressure of 2.67 with a p-value of 0.001 and a significance level of <0.05. Conclusion: There is a difference in blood pressure reduction in pregnant women with gestational hypertension in the first and third trimesters who were given boiled chayote and antihypertensive medication and those who were given antihypertensive medication at the Cidaun Inpatient Community Health Center in 2025.